2021
DOI: 10.1007/s00424-021-02598-z
|View full text |Cite
|
Sign up to set email alerts
|

The (pro)renin receptor (ATP6ap2) facilitates receptor-mediated endocytosis and lysosomal function in the renal proximal tubule

Abstract: The ATP6ap2 (Pro)renin receptor protein associates with H+-ATPases which regulate organellar, cellular, and systemic acid–base homeostasis. In the kidney, ATP6ap2 colocalizes with H+-ATPases in various cell types including the cells of the proximal tubule. There, H+-ATPases are involved in receptor-mediated endocytosis of low molecular weight proteins via the megalin/cubilin receptors. To study ATP6ap2 function in the proximal tubule, we used an inducible shRNA Atp6ap2 knockdown rat model (Kd) and an inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Recently, it has been reported that megalin in proximal tubules is working as a novel endocytic receptor for renin and prorenin. In vitro experiments discovered that endocytosis of renin and pro-renin by megalin is accompanied with (P)RR by Sun et al [ 20 ] and others [ 21 , 22 ], suggesting limited roles of (P)RR for renin/prorenin binding in tubules. This evidence indirectly might be relevant to our findings that (P)RR and renin/prorenin are tenously related physiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that megalin in proximal tubules is working as a novel endocytic receptor for renin and prorenin. In vitro experiments discovered that endocytosis of renin and pro-renin by megalin is accompanied with (P)RR by Sun et al [ 20 ] and others [ 21 , 22 ], suggesting limited roles of (P)RR for renin/prorenin binding in tubules. This evidence indirectly might be relevant to our findings that (P)RR and renin/prorenin are tenously related physiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the binding of prorenin to PRR also induces intracellular signaling such as the p38 MAPK/HSP27 pathway in cardiomyocytes independently of IGF2R and AngII, 51 resulting in alterations in actin filament dynamics, and thereby the severe cardiac hypertrophy 52 . Thus, we propose that PRR‐mediated internalization of prorenin may be apart from megalin and IGF2R, but megalin‐mediated uptake of prorenin requires PRR 4–6 . In addition, AT1 receptor‐mediated endocytosis of AngII from blood may also contribute to the accumulation of AngII that plays an important physiological role in cardiomyocytes 53…”
Section: Pathophysiological Functions Of the Cardiac Prrmentioning
confidence: 93%
“…52 Thus, we propose that PRR-mediated internalization of prorenin may be apart from megalin and IGF2R, but megalin-mediated uptake of prorenin requires PRR. [4][5][6] In addition, AT1 receptor-mediated endocytosis of AngII from blood may also contribute to the accumulation of AngII that plays an important physiological role in cardiomyocytes. 53…”
Section: Cardiac Prr May Be Correlated With the Progress Of Salt-indu...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, Figueiredo et al [2] investigated the role of ATP6ap2 in receptor-mediated endocytosis in the proximal tubule. Using two different models, the authors showed that depletion of ATP6ap2 resulted in proteinuria and increased urinary excretion of three megalin ligands.…”
mentioning
confidence: 89%